The Effect of Agility Drill Training on Agility Dribbling Techniques of Young Female Football Players - Fatoni Yanuar Akhmad Budi Sunaryo; Sugiyanto Sugiyanto; Hanik Liskustyawati; Slamet Riyadi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to examine the differences in the impact of variations in agility drills with ladders and wickets on agility dribbling techniques in young women's soccer players. Thirty-six people act as the research population who are young female soccer athletes aged 13-18 years and living in Surakarta. This study uses random sampling to determine the research sample of 32 people. Meanwhile, the research design used was experimental research with a 2x2 factorial design. Researchers apply a treatment combined with pre-test and post-test to obtain research data. In addition, the Illinois Agility Test with Ball is the research instrument used in this study. This study uses ANOVA as a data analysis technique. According to the study findings, there is a finding that the effect of the hurdles agility training method is higher when compared to the ladder drill agility training method. This finding is evidenced by the results obtained from the ANOVA test that there is a significant difference in the effect because the significance value of p is 0.005 <0.05, and the F value is 9.498. Thus, the researcher concludes that there is a significant difference in the impact of variations in goal agility training methods and ladder drill agility on the agility of the dribbling technique of young women's soccer players. Researchers hope that the findings of this study can help players and coaches improve training methods so players can develop their agility dribbling techniques optimally. Keywords: Agility dribbling technique, Agility drill training, Young female football players.